A new species of Isocapnia (Plecoptera: Capniidae) from China, with notes on I. apicispina Chen & Du, 2017 and I. arcuata Zhiltzova, 1975 - Yang, Xiao; Du, Yu-Zhou (Zootaxa, 2024)
This study describes and illustrates a new species of Isocapnia Banks, 1938, I. niuerheensis Yang & Du, sp. nov., from the Inner Mongolia Autonomous Region, China with a comparison between morphologically related species I. apicispina Chen & Du, 2017 and I. arcuata Zhiltzova, 1975.